Survival analysis of diabetes mellitus and cardiovascular patients with COVID-19: a secondary data analysis - Nugroho, Ariyanto; Fadlilah, Siti; Susanto, Herry; Damayanti, Santi; Suharto, Agus; Sugiyarto, Sugiyarto (Public Health of Indonesia, 2024)
Background: Patients with diabetes mellitus (DM) and cardiovascular disorders who suffer from COVID-19 may have an increased risk of death.  Objective: This study aims to analyze the time of death and influencing factors in patients with DM and cardiovascular disorders with COVID-19. Methods: We used a retrospective observational cohort study using medical records of COVID-19 patients treated at Dr Soeradji and Penembahan Senopati hospitals from March 2020 to June 2022. There were 2,959 participants: patients without comorbidities, with DM, and with cardiovascular problems. We extracted sociodemographic and clinical data on patient characteristics using medical records. Data analysis used Kaplan-Meier and Cox regression analysis to estimate survival probability and investigate predictors of death with a 5% significance level. Results: The median survival time was highest in the group without comorbidities (70.00) and lowest in the DM+others group (21.75). Years of treatment, age, presence of comorbidities, and type of hospital were related to the survival rate of COVID-19 patients (p<0.05). Diabetes mellitus and cardiovascular system disorders are significantly associated with survival of COVID-19 patients (p<0.001). There were significant differences between patients without cardiovascular disorders and patients with cardiovascular disorders (Non-Hypertension, Hypertension, and Hypertension + Others) adjusted by year, gender, age, and hospital type (p<0.001). There were significant differences between patients without DM and patients with DM (DM only, DM+Hypertension, and DM+Others) adjusted by year, gender, age, and hospital type(p<0.001). Conclusion: Years of treatment, age, gender, comorbid DM, and cardiovascular problems are associated with the survival rate of COVID-19 patients. Older age, DM patients who have comorbidities other than hypertension, and patients with cardiovascular issues other than hypertension show a greater risk of death than other groups. Key words: COVID-19, Diabetes Mellitus, Hypertension, Cardiovascular Diseases, Survival Rate.